INVESTIGATING ENGLISH LANGUAGE TEACHERS IN DEVELOPING TPACK AND MULTIMODAL LITERACY - Drajati, Nur Arifah; Tan, Lynde; Haryati, Sri; Rochsantiningsih, Dewi; Zainnuri, Hasan (Indonesian Journal of Applied Linguistics, 2018)
Technology in every field is snowballing. Likewise, the use of technology in education requires knowledge and understanding of English teachers. The fact that most of the technology for enhanced language learning workshop did not continue into the classrooms. Another case is that teachers do not want to use technology at all in their classrooms because of lacking time and facilities. TPACK namely Technological Pedagogical Content Knowledge provides insight for pre-service teachers and in-service teachers of English to optimize three things for education; those are the aspect of technology, pedagogy, and content knowledge. With the use of this learning model, excellent technology, pedagogy, and knowledge will support and produce a comprehensive learning process. The purpose of this study was to examine the perception and implementation of pre-service teachers and in-service teachers about the literacy of the three above aspects. By using quantitative research, we get the data from questionnaires of 100 pre-service teachers and in-service teachers. The findings describe the demographic teacher with technology, pedagogy and content knowledge literacy (TPACK). The three points of the TPACK literacy are Pedagogical Content Knowledge for Multimodal Literacy, Technological Pedagogical Knowledge (21st C Learning), and Knowledge about digital media tools. The implications of this research give direction and the alternatives to the implementation of the TPACK model for English classroom. In future, it provides the advantages to developing the quality of English teachersâ€™ professional development.Â Keywords: